Restoring the Countryside: George Perkins Marsh and the Italian Land Ethic (1861-1882). (1st February 1998) - Hall, Marcus
Abstract : G.P. Marsh wrote his monumental Man and Nature (1864) almost entirely in Italy, where he drew heavily from Italian insights and Italian landscapes. While warning about the human propensity to degrade nature, he also maintained hope in the human ability to restore nature. In Italy, as in the United States, Marsh's writings helped stimulate discussion leading to major new land-use policies; generally preservationist measures in the U.S. and restorationist measures in Italy. The novelty and urgency of Marsh's messages depended upon contrasting Old and New World traditions of land management.